(untitled) (Tarbiyah Suska Conference Series, 2024)
This research aimed at testing an influence of learning environment toward student learning achievement on Islamic Education Subject at Senior High School of PGRI Pekanbaru. It was quantitative research. All Muslim students of Senior High School of PGRI Pekanbaru were the population of this research and they were 155 students. The samples of this research were 30% of the population or 46 students. The techniques of collecting the data were questionnaire and documentation. The technique of analyzing the data was Product Moment Correlation. Based on the data analysis, it obtained that robserved 0.668 was higher than rtable at 5% significant level (0.297) or at 1% significant level (0.384), so Ha was accepted and H0 was rejected. It means that there was a significant influence of learning environment toward student learning achievement on Islamic Education Subject at Senior High School of PGRI Pekanbaru. The contribution of learning achievement toward student learning achievement was 44.7% and the rest 55.3% was influenced or described by other variables.